Organizational Identity for Cross-border Digital Trade: Achieving Technical and Legal Interoperability Within the Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services (MLIT) Using the vLEI - Marin, Ivan; Castellani, Luca G. (UNNExT Working Paper, 2025)
Identity management is a cornerstone of digital trade and a core component of trust services, starting with electronic signatures. However, there is limited awareness of its legal and technical implications. The United Nations Commission on International Trade Law (UNCITRAL) has prepared a Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services to provide uniform guidance on how to establish an enabling legal environment for identity management and trust services. The Global Legal Entity Identifier Foundation (GLEIF) has developed the Legal Entity Identifier (LEI) and its digital counterpart the verifiable LEI (vLEI) as universal solutions for a secure and cost-effective persistent business identifier. This paper illustrates how the MLIT and the vLEI may interact to provide legal and operational certainty to identification needs, thus fostering global economic growth.
Keywords: Digital cross-border trade; Digital trade; GLEIF; LEI; Legal entity digital identity; MLTR compliance; Trade facilitation; vLEI verifiable credential

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Global Arbitration Review, 2025)

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (Global Arbitration Review, 2024)

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (ICTD Working Paper, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability

Etude sur les mécanismes de justice coutumière et les modes alternatifs de règlement des conflits au Burkina Faso - Moriceau, Julien; Ouattara, Fako; Bangali, Lamissa (Ministère de la Justice et des Droits humains, chargé des Relations avec les Institutions, 2023)
Keywords: Burkina Faso; Justice coutumière; MARC ( mode alternatif de réglement des conflits ); MARD

Assessment Report of Arbitration Centre in Egypt (CRCICA) - SNFI (African Development Bank, 2022)

Lignes directrices de l'UA sur l'élaboration d'accords bilatéraux de travail (ABT) - Comité Technique Spécialisé sur le Développement Social, le Travail et l’Emploi (Union Africaine, 2022)

COFOLA International 2022: Current Challenges of Resolution of International (Cross-Border) Disputes (Publications of the Masaryk University, theoretical series, editions Scientia, 2022)
- Bridging the Public-Private Law Divide in the Conflict of Laws; - New Practices in Alternative Dispute Resolution: New Pathways to Peace; - The Singapore Convention: A Giant Leap for Mediation or Just Too Good to Be True; - Potential Nexus Between the Enforceability of Foreign Judgments and the Quality of Civil Justice in ASEAN Did the Preliminary Objections Judgment Resolve the Chagos Archipelago Sovereignty Dispute? - The Order of Periodic Penalty Payments by the CJEU in Cases Filed by a State Against Another State; - The Dichotomy of Obligations of Conduct and Result in International Investment Law; - Investment Arbitration Reform: Third-Party Funding in Investment Arbitration; - Between Protection and Access to Justice: On the Regulation of Returns in Third-Party Litigation Funding; - Contract Adjustment in Arbitration : Should the Approach Be Adjusted? - Current Challenges of Enforcing Annulled Arbitral Awards; - Condifentiality of Arbitral Awards on National, International and Institutional Level; - Digitalisation of Judicial Cooperation in the EU: A Long Road Ahead; - Resolving Cross-Border Consumer Disputes: The Digital Experience in China; - Law Applicable to Non-Consumer Contracts Concluded at an Electronic Auction; - Can Robot Judges Solve the So-Called “Hard Cases”? - Current Challenges of Cross-Border Disputes in Slovakia : Is Slovak Law Anchored in the 21st century

Les sociétés coopératives d’intérêt collectif (SCIC) et les coopératives d’activité et d’emploi (CAE) - Pelosse, Hélène; de Crevoisier, Louis; Branchu, Christine; Muscatelli, Aude (Inspection générale des Finances, 2021)

Enjeux juridiques du télétravail transfrontalier - Chikoc Barreda, Naivi; Bernstein, Stéphanie (Conseil de recherches en sciences humaines, 2021)
Le télétravail transfrontalier, une pratique qui se développe depuis plusieurs années dans le contexte du processus accéléré de numérisation de l'économie et qui a reçu une impulsion incontestable en raison de la pandémie mondiale de COVID-19, se profile comme une tendance d’avenir. La dématérialisation du lieu de travail entraînant par essence un effacement des barrières spatiales, la prestation de travail exécutée à distance se déplace en continu à travers les frontières nationales par le biais des technologies de l'information et de la communication. La modification transfrontalière du domicile ou de la résidence du salarié pendant la durée du contrat est aussi une difficulté incontournable à laquelle sont confrontées les parties, un tel déplacement pouvant conduire au changement de régime applicable, sans que ni l’employeur ni l’employé en aient prévu cette conséquence. Face à ces problématiques, il s'impose d'examiner le cadre juridique applicable au télétravail comportant une dimension transfrontalière pour déterminer dans quelle mesure il permet de répondre aux principaux enjeux de cette pratique en expansion. Nous analysons les questions relatives à la détermination de l'autorité compétente pour connaître des litiges impliquant des télétravailleurs transfrontaliers et aux modes d’identification de la loi applicable parmi celles pouvant intervenir pour réglementer les droits et les obligations du travailleur et de l'employeur dans les rapports internationaux et interprovinciaux au Canada, ainsi que la façon dont les normes minimales d'emploi de l’Ontario, de la Colombie-Britannique, de l'Alberta et du Québec appréhendent le télétravail transfrontalier, leurs conditions territoriales d’application et leurs limites.
Keywords: Compétence internationale; Conflict of laws; Conflit de lois; Contrats internationaux; Lieu d'exécution du travail; Loi applicable; Mobilité internationale; Nomades numériques; Normes minimales d'emploi; Territorialité; Télétravail transfrontalier

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future (Publications of the Masaryk University, theoretical series, editions Scientia, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

Les entreprises et l'après crise de Covid-19 : un nouveau modèle d'organisation agile entre efficience et résilience - Sinapin, Marie Noeline (LITEM, Univ Evry, IMT-BS, Université Paris-Saclay, 2020)
Les entreprises traversent une crise sanitaire sans précédent, cette crise affecte sa survie et son organisation. Elle oblige les entreprises à se réinventer à faire preuve d'imagination pour transformer une menace en opportunité, et de devenir agile. Derrière cette crise de Covid-19, il est probable qu'une crise économique pointe ses contours: Chômage partiel, récession,faillite, récession et impacts directs et indirects inconnus.Comment surmonter cette crise d'un genre nouveau et résister à ses chocs imprévisibles ? Comment transformer l'entreprise et accompagner le changement ?Pour répondre à ces questions, les travaux de recherche autour du prisme de l'efficience et de la résilience peuvent-ils apporter des outils aux entreprises, afin de rebondir ?
Keywords: COVID-19; Efficience; Pandémie; Résilience

Fiscal Potential and Political and Institutional Constraints to Increasing Domestic Revenues - Niang, Birahim Bouna; Mbaye, Ahmadou Aly (Center for Global Development, 2020)